Performa Ayam Broiler dengan Pemberian Serbuk Pinang sebagai Feed Aditive - Ulupi, N.; Inayah, S. K. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
One of the weakness of broiler chicken is susceptible to disease infection. Therefore in its feed is added by feed additive. The feed additive that is often used was antibiotics growth promoters. To produce the healthy of chicken meat, using antibiotics in feed should be avoided. The powder of areca nut contain of high flavonoid, so it can be given to broiler chicken, for replace the role of antibiotic in feed.So the purpose of this study was to evaluate the powder of areca nut in broiler chicken feed toward the production performance and its economic value. 96 day old chicks of broiler were used. They were placed at 12 swath (sized 1x1 m2) in open house, then they were distributed into 4 treatments. Every treatment consist of 3 repeted. The treatments were the level of powder of areca nut in feed, 0, 1, 2, and 3% (P0, P1, P2, and P3). Production performances were analyzed statistically, while the value of  income over feed and chick cost were analyzed descriptively.Production performances include the average of feed consumption, body weight gain, final body weight, feed conversion ratio, and mortality of broiler chickens were not significant. There were no death chicken at P1. The high value of income over feed and chick cost wereachieved by P1, in the amount ofRp7080/chicken. It can be concluded that the level of powder of areca nut in amount 1% in commercial broiler feed gave the best result.Keywords : broiler chicken, powder of areca nut, production performance, income over feed and chick cost